The Morel-Lavallée Lesion as a Rare Differential Diagnosis for Recalcitrant Bursitis of the Knee: Case Report and Literature Review - Ivor S. Vanhegan; B. Dala-Ali; L. Verhelst; P. Mallucci; Fares S. Haddad (Case Reports in Orthopedics)
A 72 year-old-male was referred to our institution with recalcitrant prepatellar bursitis. The injury was sustained after striking his right knee against a post whilst horse riding 9 months ago. Previous treatments included repeated aspiration and excision of the bursa with elastic compression bandaging. A diagnosis of a Morel-Lavallée internal degloving injury was made, and the lesion was satisfactorily managed by an internal quilting procedure to eliminate the potential dead space. A review of the literature reveals 29 published reports of Morel-Lavallée lesions with sufficient information for inclusion. These came from 14 separate countries with a total of 204 lesions in 195 patients. The most common anatomical location was the greater trochanter/hip (36%), followed by the thigh (24%) and the pelvis (19%). Most were managed surgically with evacuation of the haematoma and necrotic tissue followed by debridement, which was often repeated (36%). Conservative treatment with percutaneous aspiration and compression bandaging was the next most common treatment (23%). The knee was the fourth most common region affected (16%), and only 3 other lesions in the literature have been managed with a quilting procedure.